Effect of 6-week karate (kihon) and basic movement exercise on balance performance in visually impaired individuals - Pekel, Aylin Özge; Suveren, Ceren; Arslan, Yasin; Yavaşoğlu, Belma; Beykumül, Ayşegül; Ayyıldız Durhan, Tebessüm; Ceylan, Levent (Frontiers in Physiology, 2023)
Today, the participation of visually impaired individuals in sportive activities is essential. Because the ability to move independently starts to develop with a delay in visually impaired individuals. Physical activity is necessary to compensate for developmental delay, eliminate the problem of independent movement in social life by reducing obstacle perception problems, develop self-confidence, and provide regular muscle activation and motivation to move. The study investigated the effect of 6 weeks of karate (kata) and basic movement training on balance performance in individuals with congenital visual impairment. Fifteen visually impaired individuals aged between 10 and 14 participated in the study, and three groups were formed: experiment 1, experiment 2, and the control group. After the pretests were taken, the experimental groups received karate and basic movement training in addition to physical education classes for six weeks, while the control group continued only physical education classes. When the study results were examined, there were highly significant differences between the pre and post-test values of the groups receiving karate and basic movement training. At the same time, no progress was observed in the control group. In the post-test comparison of the karate and control groups, positive significance was found in the values of the karate group. In the same way, in the posttest comparison of the primary movement group and the control group, positive progress was made in the direction of the direct movement training group. The posttest comparison of the basic movement training and karate groups was the same.As a result, it was concluded that basic movement training and karate exercises applied for six weeks positively affected the balanced development of visually impaired individuals aged 10-14 years. No difference was found between the exercise protocols regarding effectiveness, and no improvement was observed in individuals who did not participate in any exercise.